Can changing schools help peer-victimized students escape their plight? A mixed-methods study - Tenhunen, Essi-Lotta; Kuusiaho, Inka-Liisa; Salmivalli, Christina (SAGE Publications, 2025)
Changing schools tends to be more frequent among victimized students and is sometimes used as a means to put an end to persistent bullying. However, whether these changes benefit victimized students remains unclear, as bullying victimization often persists across different contexts. This mixed-methods study (n = 58,799 and n = 68 for quantitative and qualitative data, respectively) conducted in Finland examines the role of victimization history in the association between newcomer status and victimization in the new school among elementary school students (fourth to sixth graders, that is, 10–12 years old) and middle school students (seventh to ninth graders, that is, 12–15 years old). The findings showed that elementary school newcomers with most frequent victimization history seemed to benefit from the school change compared to established students with similar victimization histories. A corresponding, albeit much weaker, effect was observed among middle schoolers. Previously victimized students had initially been more willing to change schools than non-victimized students. The qualitative content analysis showed a more complex reality—some of the previously victimized newcomers had strong aspirations for a better future, while others experienced fears and losses of established friendships. Eventually, the school change can bring both disappointments and rewards, depending on the newcomers’ ability to make new friends and escape bullying.